Genetic diversity between the wheat varieties Triticum aestivum L.and the effect of temperature on germination characteristics. - Ramadan, S. A. Ahsyee, Alramah, A. A. Saed (Journal of Pure & Applied Sciences, 2019)
A laboratory experiment was conducted during 2017 at the laboratory of the faculty of science at university of  El-Zentan in Libya, to determine the germination capacity of bread wheat seed (Triticum aestivum L.) for five varieties ( Bohot 208, Abu Alkhair, Sham10 and Exad 901) under the effect of three temperature (10, 20 and 25C? ). A completed randomized design with four replications in tow factors. The results showed that 25C? gave the higher averages of germination percentage, radical length and plumule length (83.5%, 11.45cm and 9.83cm) respectively, while 10, 20 C? recorded the higher averages of seedling dry weight (0.66g). Abu Alkhir seeds gave the highest averages of germination percentage and radical length (95.3% and 10.5cm) respectively. The varieties varied in germination percentage and seeding characters at different temperatures degrees. Specifically Sham10 gave the higher average of the plumule length and radical length with cultivar of Abu Alkhair 10.5cm. While the higher average of dry weight was recorded to Exad901 (0.66g) significant positive correlation was found between each of the plumule length and radical length also between temperature and the length of plumule and radical, while a negative correlation was found between temperature and dry seedling.